Measurements of SiH4/H2 VHF Plasma Parameters with Heated Langmuir Probe. Issue 8 (20th September 2013) - Yamane, T.; Nakao, S.; Takeuchi, Y.; Muta, H.; Ichiki, R.; Uchino, K.; Kawai, Y.
Abstract The parameters of a SiH4/H2 VHF plasma were measured as a function of silane gas concentration with a heated Langmuir probe. It was found that when the sailane gas concentration is increased, the nagative ion density increases. Here the negative ion density was estimated from the reduction of the electron saturation current. In addition, the dependence of the wall potential on the silane gas concentration agreed with the theoretical values derived from the Bohm sheath equation including negative ions. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)